The Making of Islamic Education in Lombok-Indonesia: Genealogy, Transformations, and Ideology - M. Habib Husnial Pardi; Muhammad Said; Adibah Sulaiman (SYAMIL: Journal of Islamic Education, 2024)
This study aims to investigate the role of Tuan Guru in the making of Islamic Education through genealogical analysis, transformation, and ideology of Islamic education from the beginning to the modern era in Lombok. This study uses qualitative case studies to explore the topic and uses purposive sampling to select three Islamic educational institutions as objects in Lombok. Data was collected through a combination of observation, in-depth interviews, and reviews of relevant literature. The study identifies three findings: first, the establishment of Islamic education in Lombok in line with the Islamization process in the 17th-18th centuries. The early form of Islamic education in Lombok is Santren; a nonformal institutions with tarekat curricula. Second, along with the strengthening of the modern educational of the Dutch East Indies, the madrasa system emerged by the role of Middle Eastern alumni the so-called Tuan Guru. Tuan Guru built madrasa as center of Islamic learning and struggle against Colonial. Third, in post authoritarianism of New Order, Islamic boarding schools developed with various ideologies and transformation, such as traditional Pondok Pesantren managed by Aswaja circles (NW and NU), integrated modern-Islamic (Sekolah Islam Terpadu) managed by modernists and Salafi-Wahhabi groups.